2014
DOI: 10.16970/ted.41111
|View full text |Cite
|
Sign up to set email alerts
|

Study on species composition of Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) on cotton in Çukurova plain, Turkey

Abstract: Study on species composition of Bemisia tabaci (Gennadius, 1889)(Hemiptera: Aleyrodidae) on cotton in Çukurova plain, Turkey 1Çukurova'da pamukta bulunan Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae)'nin tür kompleksi üzerine çalışmalar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…; Karut et al. ). In addition to these invasive species, the Asia 1 (M biotype) was reported in Turkey by Bedford et al.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Karut et al. ). In addition to these invasive species, the Asia 1 (M biotype) was reported in Turkey by Bedford et al.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we have collected several B. tabaci samples from greenhouses that were analysed with the samples collected from cotton fields used in earlier studies (Karut et al. ). Based on DNA analyses, we found that there are important differences in the nucleotide sequences in some populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations